Analysis of the standard of performance in young male and female triathletes - Peter, P.; Marque, F.; Oberhoffer, R.; Schönfelder, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Triathlon has a short history, but result lists show that the quantity of young participants in triathlon competitions is growing from year to year. Scientifically gained data of young triathletes, however, is practically lacking. Thus, the aim of the present study was to develop a standardized and triathlon specific test battery for annual talent scouting of the Bavarian triathlon association to gain performance reference data to screen and standardize performance of young male and female triathletes. Methods: A triathlon-specific test battery has been applied as a standardized test procedure in several talent scouting workshops to gain long-term data from young triathletes. The present test battery contained anthropometric measurements, sub-distance tests in swimming and running, a criticalpower-test on cycle ergometer, basic sport-motoric tests and a questionnaire measuring the performance motivation. Additionally, training and competition data of the young athletes have been collected. In sum, 185 male and 131 female Bavarian triathletes at the age of 10 to 19 years took part in the talent detection workshops from 2009 to 2013. Results: Mean swim performance over 400m ranged from 0.87 ± 0.08 m/s to 1.09 ± 0.22 m/s (10 to 19 years). Mean running performance over 1000m ranged from 4.3 ± 0.3 m/s to 5.3 ± 0.5 m/s (10 to 19 years). Successful triathletes showed better abilities in sub-distance performance in swimming and running and spend more hours for training than their coeval counterparts. The physique of squad triathletes seems to be more ectomorphic, thus taller and thinner than the shape of non-squad athletes. Results of a correlation analysis showed positive correlations of limb length and swimming and running performances. Significant correlations (p<0,05) have been found for running performance and reactive jump abilities. Discussion: The gained performance data gives meaningful indications for the performance abilities of young, new blood triathletes and set complex standards for their future training goals. The results for anthropometric and performance data showed similar results to data from adult triathletes (Sleivert and Rowlands, 1996; Landers et al. 2000). Sub-distance performances were analyzed before by Moeller et al. (2008) in young elite athletes with assimilable results. In sum, using the present reference data will improve talent scouting in future showing a more differentiated shape of young triathletes.